3(2x+1)-5=6x-2

Simple and best practice solution for 3(2x+1)-5=6x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x+1)-5=6x-2 equation:


Simplifying
3(2x + 1) + -5 = 6x + -2

Reorder the terms:
3(1 + 2x) + -5 = 6x + -2
(1 * 3 + 2x * 3) + -5 = 6x + -2
(3 + 6x) + -5 = 6x + -2

Reorder the terms:
3 + -5 + 6x = 6x + -2

Combine like terms: 3 + -5 = -2
-2 + 6x = 6x + -2

Reorder the terms:
-2 + 6x = -2 + 6x

Add '2' to each side of the equation.
-2 + 2 + 6x = -2 + 2 + 6x

Combine like terms: -2 + 2 = 0
0 + 6x = -2 + 2 + 6x
6x = -2 + 2 + 6x

Combine like terms: -2 + 2 = 0
6x = 0 + 6x
6x = 6x

Add '-6x' to each side of the equation.
6x + -6x = 6x + -6x

Combine like terms: 6x + -6x = 0
0 = 6x + -6x

Combine like terms: 6x + -6x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 0.06(y-9)+0.04y=0.08y-0.01(60) | | 1/3+10u=y/v | | 6=-2910n+7 | | 8-(3+7)=23 | | 0.4x+56000(0.2+x)=1400 | | B=xm+m | | 2y^3+2+6y^2+6y= | | 4(3+5x)=47 | | 5p-13=8p+4 | | 5x-3+3(2x+2)=-3(x+3) | | tn=5n+7 | | 7x+8x=13x | | 6x+7-2x=19 | | 5x+7(x-1)=-3 | | 2y-6=2x | | 5a+10=3a+10 | | x+(x*0.07)=35.19 | | 14(t-6)+4t=6(3t+5)-8 | | (6x-6)-(13x+8)= | | 3x-5(x-3)=16-4x | | x+(x*0.07)=28.25 | | -13x=234 | | -(4y+4)-(-3y-8)=-2 | | 1/4+3/8x=3/4 | | 3.5+0.75x=17.00 | | 10x+5/2y=20 | | 2x-1-.5-6x-x= | | x+(x*0.07)=131.8 | | 8/3x+1/3x=5x+65/3+7/3x | | -2(3s-1)-2=-2(5s+6)-2 | | x+8=38 | | -20x+5(2-3x)=40-6x |

Equations solver categories